2014
DOI: 10.5717/jenb.2014.18.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of walking exercise on abdominal fat, insulin resistance and serum cytokines in obese women

Abstract: [Purpose]The purpose of the study was to investigate the effect of 12-week walking exercise on abdominal fat, insulin resistance and serum cytokines in obese women.[Methods]Following baseline measurements, obese women (N = 20) who met obesity criterion of BMI at 25 kg/m2 or greater were randomly assigned to the control (n = 10) or exercise groups (n = 10). Women assigned to the exercise group participated in a walking exercise (with an intensity of 50-60% of predetermined VO2max, a frequency of 3 days per week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 45 publications
7
31
0
2
Order By: Relevance
“…Whether the HR during the walking exercise reached the target HR was confirmed using the Polar heart monitor. [26] They found that the exercise led to significant reductions in both subcutaneous and visceral adiposities in consistent with our study. We believe that using a pedometer giving instant personalized audible feedback is simpler and user-friendly approach.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Whether the HR during the walking exercise reached the target HR was confirmed using the Polar heart monitor. [26] They found that the exercise led to significant reductions in both subcutaneous and visceral adiposities in consistent with our study. We believe that using a pedometer giving instant personalized audible feedback is simpler and user-friendly approach.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we showed that 12-week walking exercise with the sufficient moderateintensity provided with the association between the HR and pedometer step counts resulted in the decrease in abdominal obesity. [14] Recently, Hong et al [26] investigated the effect of 12-week walking exercise on abdominal fat in obese women. The walking exercise was performed at the exercise intensity as 50 to 60% of VO 2 max.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome measures were aerobic fitness expressed as VO 2max (mL/kg·min), body mass (kg), body fat (%), BMI (weight in kilograms divided by height in metres squared), waist circumference (cm), waist-to-hip ratio, systolic and diastolic blood pressure (mm Hg), total cholesterol (mmol/L), high-density lipoprotein (HDL) cholesterol (mmol/L), low-density lipoprotein (LDL) cholesterol (mmol/L), triglycerides (mmol/L) and fasting glucose (mmol/L). Outcomes for insulin resistance and inflammation-related serum cytokines,45 blood flow in lower extremities,46 arterial stiffness,48 postural stability,42 bone mineral density42 and biomarkers of endothelial function49 were not included in the meta-analyses because of insufficient number of comparisons (<10) (see Higgins and Se54). …”
Section: Methodsmentioning
confidence: 99%
“…The health crisis resulting from the adiposity that appears at these specific anatomical locations has been termed “metabolic obesity” [2]. The effective elimination of excessive abdominal fat in obese people through lifestyle modification and adjuvant appetite suppressants has been associated with reductions in fasting plasma glucose, triglycerides, and HOMA score [3]. Such beneficial effects on the parameters of metabolic syndrome induced by visceral fat reduction were more noticeable compared with those resulting from subcutaneous fat reduction [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is robust evidence that high-volume, moderate-intensity continuous training (MICT) with exercise sessions ≥ 45 min can reduce abdominal visceral fat [3, 57] as well as improve body composition, cardiovascular fitness, and other health-related parameters including insulin sensitivity and lipid profile in both healthy and obese people [8, 9]. More recently, high-intensity interval training (HIIT), which consists of repeated high-intensity exercise bouts interspersed with passive/active recovery, was shown to induce similar metabolic adaptations associated with continuous training among healthy populations [10], as well as in patients with chronic diseases [11–13].…”
Section: Introductionmentioning
confidence: 99%